Visible-light-induced decarboxylative sulfonylation of cinnamic acids with sodium sulfinates by using Merrifield resin supported Rose Bengal as a catalyst. Issue 22 (22nd May 2019) - Li, Pinhua; Wang, Guan-Wu
Abstract : An efficient resin-supported RB catalyst was prepared for the visible-light-induced decarboxylative sulfonylation of cinnamic acids with sodium sulfinates. Abstract : A visible-light-induced decarboxylative sulfonylation of cinnamic acids with sodium sulfinates for the synthesis of vinyl sulfones was developed. The reaction proceeded smoothly in the presence of Merrifield resin supported Rose Bengal ammonium salt as a photocatalyst and tert -butyl hydroperoxide (70% in water) as an oxidant in aqueous DMSO solution at room temperature under green LED (530–535 nm) irradiation under an air atmosphere, generating the desired products in good yields. Notably, the supported catalyst can easily be separated from the reaction mixture by filtration and can be recycled at least six times without any significant loss of activity.